2011
DOI: 10.1386/jams.3.2.263_1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the 'Leapfrog' debate in light of current trends of mobile phone Internet usage in the Greater Johannesburg area, South Africa

Abstract: At first glance, mobile technology appears to have the potential to allow countries in Africa to technologically 'leapfrog' across the digital divide and provide much needed Internet access to a wide range of people currently unable to participate in the Information Society. This study investigates whether this potential is being actualized through the survey of a non-purposive sample population living in Johannesburg, South Africa. Studies have shown that aside from being able to engage with the new technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Several studies have highlighted deficiencies between smartphones and PCs. For example, one study found that memory and storage capacity limitations were frequently cited reasons for why smartphones cannot completely replace PCs (Hyde-Clark & van Tonder, 2011). Content issues are also a factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have highlighted deficiencies between smartphones and PCs. For example, one study found that memory and storage capacity limitations were frequently cited reasons for why smartphones cannot completely replace PCs (Hyde-Clark & van Tonder, 2011). Content issues are also a factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Africa the minimum infrastructure for the use of e-mobile and technology applications are lacking, for instance electricity supply is non-existent or not consistent. The critical need of internet resources and application become futile due to poor electricity supply and in some circumstances failure of supply for a prolong period of time [19]. This situation leads to inaccessible of the necessary Internet browsing or e-mobile courseware.…”
Section: Readiness Of Developing Countries' Use Of Modern Technologymentioning
confidence: 99%
“…In addition, different types of usage are characterized by various levels of quality and complexity (Hyde-Clark & Van Tonder, 2011;James & Versteeg, 2007). If somebody borrows, for example, a mobile phone to make a call or uses a mobile phone kiosk, it means that this person can make a call, but cannot receive a call at any time.…”
Section: Usage Of Mobile Phones In Africamentioning
confidence: 99%
“…In addition, it is widely believed that the proliferation of ICTs within a nation state or a society and the concomitant integration with the information society will have positive social and economic consequences as it will, among others, raise productivity, increase work opportunities, contribute towards the spread of information and knowledge, and in general foster development and raise the quality of life of the population (Van Audenhove, 2003). It is furthermore believed that the proliferation of ICTs could help developing countries to "leapfrog" stages of development towards becoming information societies (Hyde-Clark & Van Tonder, 2011). Moreover, Manuel Castells (2000Castells ( , 2001 holds that a society's economic growth and development is dependent on the spread of ICTs throughout the society.…”
Section: Introductionmentioning
confidence: 99%